Digital Accessibility as a Business Practice (Open textbook library., 2018)
Most business leaders would agree that reaching the broadest audience is good for a business’s bottom line. A good portion of that audience will be people with disabilities. How, though, would an organization go about ensuring it is as accessible as it can be to all its potential clients or customers, including people with disabilities? This book has been created to answer this question, and to demystify “digital accessibility” as a business practice. It brings together all the pieces of the digital accessibility picture, and provides strategies and resources that will help make digital accessibility a part of an organization’s business culture.